Environmental Issues in the Power Sector : Long-Term Impacts and Policy Options for Karnataka - World Bank (Washington, DC, 2014)
This study of the long-term environmental impacts and policy options for power sector development in Karnataka, is one of a series undertaken by the Bank, in cooperation with the Government of India and state governments. It is a follow-up to the broader study Environmental Issues in the Power Sector (EIPS) (ESMAP/World Bank 1998), and the general methodology developed for EIPS, is used for this analysis. The study begins by evaluating the impacts of the baseline reform scenario, and then perturbs this scenario for the options examined, including a scenario of "stalled reform," to enable assessment of the costs and benefits of reform. Because Karnataka has already implemented significant reform measures, "no reform" (as used in the original 1998 EIPS study) is not a useful scenario. The critical insight of this study is that the damage costs of emissions from grid-based fossil plants are between one and two orders of magnitude smaller than those of captive and self-generation units, emissions from which are essentially uncontrolled, and occur in more populated areas at, or near ground level. The report addresses the coal-by-wire option, which would shift from Karnataka to the producing states the environmental impacts that are associated with coal generation. It may well be that the producing states will as a result, have to impose much higher coal royalties, and, it is also likely that coal-producing areas would encounter water resource constraints: while Karnataka is a drought-prone state for which the opportunity costs of consumptive use are higher than in the eastern states of Bihar and Orissa, it is unclear if mine-mouth projects in those states could serve the bulk of the power needs of both southern, and northern India in the decade 2010-2020. The study highlights that power sector reform is the single most important step that may be taken to mitigate the environmental impacts of the power sector, while tariff reform is the second most important policy option for environmental sustainability, with demand-side management being a win-win factor. Consumptive water use for thermal generation is a major issue in Karnataka. Gas combined-cycle combustion turbines, which are attractive for their relatively low air emissions, consume only one third of the water that a steam-cycle project uses. The use of imported coal would be a viable option for Karnataka, if the existing customs duty on imported coal were to be removed. This study shows that the probable capital cost decreases for wind power, would still permit an acceptable rate of return for developers, but that the pace of new projects may slow as only the best sites will warrant development under the new tariff.